Research focus and theme trend on fulminant myocarditis: A bibliometric analysis - Yang, Weimei; He, Xifei; Wang, Zhaozhao; Lu, Lijuan; Zhou, Ge; Cheng, Jie; Hao, Xinying (Frontiers in Cardiovascular Medicine, 2022)
Aims: This study intends to explore the research focus and trends of fulminant myocarditis to have a better understanding of the topic. Methods: The data were downloaded from Web of Science(WoS) database by the topic (TS) advanced search strategy. Many instruments were used to extract, analyze and visualize the data, such as Microsoft Excel, HistCite Pro, GunnMap, BibExcel and VOSviewer. Results: 726 documents were indexed in the WoS from 1985 to 2022. The USA and the Columbia University were the most productive country and institution. Keywords co-occurrence was carried out and four research themes were identified. In addition, the top three prolific authors, the first three highly-cited authors, and the core authors of the author co-citation network were identified. The topics that they kept an eye on were analyzed and the research areas of key authors were similar to the results of keyword co-occurrence. The hot topics of fulminant myocarditis were related to the mechanical circulatory support, etiology, diagnosis, and the disease or therapy associated with fulminant myocarditis. Conclusion: This study carried out a systematic analysis of the documents related to fulminant myocarditis from 1985 to 2022, which can provide a guideline for researchers to understand the theme trend, so as to promote the future research to be carried out.